Determinant of Bank Risk in Indonesia - Adler Haymans Manurung , Benny Hutahayan , Kevin Deniswara (International Journal of Advanced Science and Technology, 2020)
This paper has objective to explore determinant of Bank Risk In Indonesia.  Model Panel Data is used to see the determinant of Bank Risk in Indonesia period 2008 to 2018. Non-Performing Loan, Loan to Deposits Ratio, Asset, Fed Rate, Oil Price and dummy variable are significantly to affect Bank Risk.   Asset was also used as moderating variable in the model. Loan Deposits Ratio, Fed Rate and dummy variable significantly affect to make relationship with Bank Risk. Keyword: Bank Risk, Non Performing Loan, Loan Deposits Ratio, Oil Price, Fed Rate, Asset, Moderating Variable.